Wakaf: Kajian Komunikasi yang Memotivasi Umat untuk Berwakaf - Nelly Nailatie Maarif; Usep Abdul Matin (JURNAL INDO-ISLAMIKA, 2019)
This paper argues that a key success of the implementation of waqf (wakaf/Islamic endowment) is the degree to which a nazir (nazhir/waqf supervisor) qualifies him/herself to develop waqf property in a trustworthy and productive way; therefore, he/she is capable of building trust of Muslim society (ummat) him/her. Additionally, success or failure of socializing and communicating this waqf execution to the society depends on the physical endowments; that is, at least the ummat know about the distribution of waqf. Here, the nazir is a key point in developing the waqf. The reason would be the fact that a prospective endower candidate often establishes fit and proper test to a nazir candidate. If the test convinces the endower candidate to trust the nazir, this candidate will automatically endow his/her own property for the sake of waqf. In opposite, if the test does not assure this potential endower, he/she will not accomplish his/her own property for the sake of waqf. This study found that a strategy of communication, which is employed by the nazir, helped convince him/her to lead the ummat to constitute the waqf of land inhabited by people of different areas. This research recommends that the nazir publicize waqf as well as Muhammadiyah organization has done it by its magazine; therefore, the ummat recognize the development of waqf, and this publicized waqf practice can become a good example of how the umat should execute their waqf programs.